Is Arab-Israeli Settlement Possible In the Lifetime of Present Generation? - V. V. Popov (Международная аналитика, 2016)
The article investigates prospects for the settlement of the Arab-Israeli conflict. In the detailed consideration of the actual state of affairs, the author refers to the history, showing how certain decisions influenced the development of the situation. Special attention is paid to the US policy in the region. The chances of a peaceful settlement are also analyzed.